2017
DOI: 10.1002/adma.201700222
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Highly Sensitive Ionic‐Polymer‐Gated WS2–Graphene Photodetectors

Abstract: been shown to operate as high-speed photodetectors [3] with response times comparable to conventional silicon-based devices, but the absence of a bandgap and lack of significant gain mechanism limits their use for ultrasensitive light detection. Hybrid structures of graphene with semiconductor materials such as quantum dots, [4][5][6] chlorophyll molecules, [7] and MoS 2 [8][9][10] have been shown to enhance light absorption and provide an internal gain mechanism. However, these implementations typically have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 50 publications
(132 reference statements)
3
99
0
Order By: Relevance
“…Some relatively 2D materials also act as main absorbing layer and trapping layer at the same time. Mehew et al reported a all 2D materials photogating photodetectors with an ionic‐polymer gate to achieve a photoresponsivity of 10 6 A/W …”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some relatively 2D materials also act as main absorbing layer and trapping layer at the same time. Mehew et al reported a all 2D materials photogating photodetectors with an ionic‐polymer gate to achieve a photoresponsivity of 10 6 A/W …”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%
“…For achieving high interfacial charge transfer efficiency, a series thickness of C 8 ‐BTBT less than exciton diffusion length are investigated in Figure D with a responsivity of 1.57 × 10 4 A/W (a gain of 10 8 ). The detection range of single layer enhanced device always limited by absorption spectrum of active layer mostly range from 400 to 700 . Therefore, the NIR sensitive materials in combination with 2D materials has raised a huge wave.…”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such low‐cost material deposition, coupled with excellent light absorption and moderate carrier transport properties, makes these layered TMD materials promising candidates for sensitive and inexpensive photodetection applications. While large responsivity has been demonstrated in layered material based photodetectors, in general, there are two important bottlenecks that limit the practical applicability of these devices. First, the response of many of the 2D devices is slow owing to long lived charge trapping in the active material as well as in the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] [7] However, in these extrinsic strategies the spectral range of the photodetector is limited by the resonance of the plasmonic structure, or the absorption edge of the semiconductor which is typically in the visible, hindering their use in broadband photodetection applications. [3] Intrinsic strategies also exist whereby a band gap is opened in graphene through functionalization with adatoms, such as fluorine and hydrogen.…”
Section: Introductionmentioning
confidence: 99%